Assessment Practices in The Implementation of the Merdeka Curriculum in Elementary Education: An Observation Study at SDN 7 Panarung - Angger Dimas Ona Giri; Aprizal Kumaunang; Aril Arista; Khusna Khusna; Mariani Mariani; Michael Alfa Febrian; Muhammad Ahyadi; Sapar Alamsyah; Laila Rahmawati (STKIP Singkawang, 2024)
The Independent Curriculum implementation requires a paradigm shift in learning assessment practices from outcome-oriented approaches toward assessment supporting continuous, student-centered learning. Assessment should function not only as a measurement tool but also as a foundation for pedagogical decision-making. However, empirical evidence regarding elementary school assessment practices within the Independent Curriculum context remains limited. This study examined learning assessment practices in Independent Curriculum implementation at SDN 7 Panarung, focusing on diagnostic, formative, and summative assessments, and the utilization of assessment results for instructional improvement. This qualitative descriptive observational study involved 12 classroom teachers (grades 1-6), students, and the school principal. Data were collected through participant observation, semi-structured interviews, and document analysis, then analyzed using triangulation techniques. Findings indicated that teachers implemented diagnostic, formative, and summative assessments aligned with Independent Curriculum principles. Formative assessment constituted the most prevalent practice, primarily through oral questioning, classroom observation, and daily assignments. However, feedback quality was generally generic rather than specific and constructive. Summative assessment employed various instruments, though written tests remained predominant and higher-order thinking skills assessment was not yet optimized. Assessment results informed remedial and enrichment activities, but implementation lacked systematic documentation. The study concluded that assessment practices at SDN 7 Panarung demonstrated general alignment with Independent Curriculum frameworks. However, continuous professional development, strengthened institutional support, and systematic assessment data utilization are recommended for enhanced implementation quality